Working With Older Adults in Integrated Health Care: Social Workers' Perspective. (October 2022) - Weng, Suzie S.; Valenzuela, Jessica
Objective: Older adults are a rapidly growing segment of the global population; a paucity of research exists on social workers supporting this vulnerable group in integrated health care that focuses on both physical and behavioral health. To fill the gap, this study explored social workers' perspectives of working with older adults in integrated healthcare settings.Methods: Using qualitative methods, a constant comparison data analysis approach was conducted to identify themes.Results: Themes included: (1) working with and highlighting the unique needs of older adults in integrated health, (2) identifying skills needed for working as a social worker within integrated healthcare settings, (3) supporting patient families, and (4) needing to make decisions on behalf of patients.Discussion: Study findings demonstrate social workers as key members of interdisciplinary team as well as highlight the unique needs, skills, and challenges for working with older adults in integrated healthcare settings.